The salience of proactive personality in academia settings - Abdul Wahat, Nor Wahiza (Eurojournals, 2009)
The work adjustment of new academics in public universities in Malaysia is now made more interesting by the calling of high performance culture by universities management. Besides the classical business of teaching, research and publishing activities are now made as part of the key performance indicators within the academia setting. Using the approach of individual differences, a qualitative study was conducted to assess the extent to which proactive personality is salient in the work adjustment of new academics within their new organizational culture. Results from the study indicated the vitality of proactive personality in the process of new academics’ work adjustment. The findings supported previous literatures on the essence of strategic planning and future-focused, initiative in making meaningful changes and concern with human relations in adjusting oneself to new job and work environment.